Graduación. (UNED, 2023)
De izquierda a derecha aparece Marcelo Blanc Macias Director Asuntos Estudiantiles, Carlos Luis Fallas Monge Vicerrector Ejecutivo, Jorge Enrique Guier Esquivel, Chester Zelaya Goodman Rector, Marco Vinicio Álvarez Amador - Vicerrector Planificación